22 5α-tetrahydrocortisone exhibits topical anti-inflammatory action with limited adverse effects on angiogenesis. (1st April 1997) - Abernethie, Amber J; Gastaldello, Annalisa; Livingstone, Dawn EW; Walker, Brian R; Hadoke, Patrick WF; Andrew, Ruth
Abstract : Glucocorticoids (GC) are potent anti-inflammatory drugs but have debilitating side effects. A safer alternative is required and 5α-tetrahydrocorticosterone (5αTHB, a metabolite of the natural rodent glucocorticoid corticosterone) may provide a solution. 5αTHB is anti-inflammatory in vivo but with fewer systemic adverse effects. It is rapidly cleared from systemic circulation and is therefore being investigated for topical application. Topical steroids additionally impair wound healing, largely due to the inhibition of angiogenesis and of collagen deposition. Here, the effects of 5αTHB on processes involved with wound repair were investigated. Angiogenesis was assessed using two murine models. In the first, sponges containing vehicle, 5αTHB (3 mg or 15 mg), or corticosterone (3 mg) were implanted subcutaneously in C57Bl6 mice (male, aged 8–12 weeks, 8–12/group). After 21 days sponges were excised and fixed, and vessel growth and collagen deposition were assessed by counting and picro-sirius red staining, respectively. At equipotent anti-inflammatory doses, corticosterone decreased the amount of collagen in sponges (3 mg changing to 30%±8% of control; p<0.05) whereas 5αTHB did not (15 mg; 128%±20%). Similarly, while corticosterone reduced new vessel growth to 15%±3% of control (p<0.05), this effect was less marked with 5αTHB (46%±7%; p<0.05) vs corticosterone. In the second model, vessel growth was stimulated from mouse aortic rings (C57Bl6 mice, male, age 8–10 weeks) and attenuation of growth was assessed following incubation with steroid (dose ranges 1 nM–10 μM, n=6–8/dose). Angiogenesis was suppressed to a lesser extent by 5αTHB (EC50 2399 nM) than by dexamethasone (8 nM) or hydrocortisone (675 nM; n=6–8/dose). These data suggest that 5αTHB could provide a safer anti-inflammatory treatment for topical application. It has fewer adverse effects on angiogenesis and collagen deposition than hydrocortisone and is thus likely to be less detrimental during wound repair.